(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the psychological image and uniqueness of the domestic, social and inner conflict of the hero in the novels of A. Qadiri, the founder of Uzbek novel writing, "O’tkan kunlar" and "Tamilla" by the French writer F. Duchene.